2023
DOI: 10.1136/bmjopen-2023-071934
|View full text |Cite
|
Sign up to set email alerts
|

Associations between human cytomegalovirus infection and type 2 diabetes mellitus: a systematic review and meta-analysis

Xiaona Wang,
Jun Chen,
Zhichao Cao
et al.

Abstract: ObjectiveMultiple studies have reported a potential contribution of human cytomegalovirus (HCMV) to the pathogenesis of type 1 diabetes and post-transplantation diabetes. However, the association between HCMV and type 2 diabetes mellitus (T2DM) remains unclear. In this paper, we employ the meta-analysis approach to investigate the potential correlation between HCMV infection and T2DM.MethodThe data of our study were collected from PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…7 Recently, cytomegalovirus has been shown to be related to T2D onset, although some evidence suggests this may not be the case for all human populations. 8 In one study, 576 adult patients with CMV disease were followed for 5 years along with 2880 controls; neither group had evidence of T2D at the outset. Over the 5-year follow-up, new-onset cases were significantly higher in the group with CMV disease compared to case controls.…”
Section: Cytomegalovirus (Cmv) Statusmentioning
confidence: 99%
“…7 Recently, cytomegalovirus has been shown to be related to T2D onset, although some evidence suggests this may not be the case for all human populations. 8 In one study, 576 adult patients with CMV disease were followed for 5 years along with 2880 controls; neither group had evidence of T2D at the outset. Over the 5-year follow-up, new-onset cases were significantly higher in the group with CMV disease compared to case controls.…”
Section: Cytomegalovirus (Cmv) Statusmentioning
confidence: 99%
“…Studies reported a heightened T1D and type 2 diabetes (T2D) incidence rates after the beginning of pandemic, surpassing pre-pandemic period 7,8,9 . In addition to SARS-CoV-2, a number of studies suggests the correlation between viral infections and T1D 10 , including enteroviruses 11 , such as coxsackievirus B 12,13 , as well as rotavirus 14 , mumps virus 15 , and cytomegalovirus 16 . Coxsackievirus B4 (CVB4), a positivesense single-stranded RNA virus, isolated from newly diagnosed T1D patients could infect and induce destruction of human islet cells in vitro 17 .…”
Section: Introductionmentioning
confidence: 99%